A Facile Route to Construct SiCO Nanospheres with Tunable Sizes. Issue 4 (22nd August 2013) - Yu, Yuxi; Wang, Han; San, Haisheng; Liu, Yu; Fang, Jiyu; An, Linan; Fang, Qingling
<x xml:space="preserve">Abstract</x> We report a facile route to synthesize SiCO nanospheres using Pluronic F127/polyvinylsilazane (PVSZ) mixed micelles as a template, in which PVSZ selectively swells with the PEO core of the F127 micelles. The thermal degradation of the F127/PVSZ mixed micelles leads to the formation of SiCO nanospheres. The size of the resultant SiCO nanospheres can be tuned in the range from 25 nm to 75 nm by controlling annealing time at 70°C.